2001
DOI: 10.1002/ijc.10106
|View full text |Cite
|
Sign up to set email alerts
|

Expression and mutation analysis of the Wilms' tumor 1 gene in human neural tumors

Abstract: The Wilms' tumor 1 gene, WT1, encodes a zinc-finger protein that is implicated in the development of Wilms' tumor. Mutant or aberrantly expressed WT1 isoforms have also been described in desmoplastic small round cell tumor, acute leukemias, mesothelioma, breast tumors and melanoma. During early development, WT1 is expressed in the brain and spinal cord, however its role in the malignancies that affect these tissues has not been previously investigated. In our study we have examined neural tumors including brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…These results indicate that WT1 is not significantly associated with the oncogenicity of NB. A previous report on WT1 gene mutation and mRNA expression also showed a consistent finding that WT1 did not play an obvious role in the pathogenesis of neural tumors, including brain tumors and NB [23]. Immunohistochemical analysis of NB and GN samples showed that ganglionic cells show higher expression of WT1 protein.…”
Section: Discussionsupporting
confidence: 52%
“…These results indicate that WT1 is not significantly associated with the oncogenicity of NB. A previous report on WT1 gene mutation and mRNA expression also showed a consistent finding that WT1 did not play an obvious role in the pathogenesis of neural tumors, including brain tumors and NB [23]. Immunohistochemical analysis of NB and GN samples showed that ganglionic cells show higher expression of WT1 protein.…”
Section: Discussionsupporting
confidence: 52%
“…21 The first laboratory investigation that focused on WT1 expression in central nervous system malignancies, including GBM, found WT1 expression in most of these tumors; yet there were no mutations affecting the zinc fingers of the gene product in tumors expressing WT1. 9 Though this appeared to indicate that WT1 expression might not have clinical relevance to the molecular etiology of brain tumors, these results nonetheless ignited a novel interest in the relationship of WT1 to central nervous system tumors. A few years later, Oji et al were able to show that the WT1 protein expression was significantly greater in high-grade tumors than in low-grade tumors and that treatment with WT1 antisense oligomers specifically inhibited GBM cell lines.…”
Section: Gbm and Wilms Tumormentioning
confidence: 99%
“…In human acute myeloid and in progressing lymphoid leukemias, high levels of expression of wild‐type WT1 have been frequently found16, 17 and may be associated with the development of more primitive and refractory forms of disease 18, 19. Furthermore, overexpression of WT1 has been reported in several other human malignancies including solid tumors of the breast,20 where it predicts poor prognosis,21 lung,22 brain,23 ovary24, 25 and skin 26. Even more important, using antisense technology, downregulation of WT1 protein has been shown to inhibit the proliferation of leukemic,27 breast28 and lung29 cancer cells in vitro .…”
mentioning
confidence: 99%